2004
DOI: 10.1007/s00383-003-1125-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistology of aquaporin-1 and stem cell factor-receptor in human undescended testes

Abstract: These results indicate a direct involvement of AQP 1 in the regulation of fluid transport across the endothelial cell membranes of testicular microvessels. A role of the C-kit receptor protein is also substantiated by its strong expression in the maturing spermatogonia of the normal testes, but was minimally or not recognizable in undescended prepubertal testes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…, 2006). As c‐kit is reported to be expressed in prepubertal human testis (Nicotina et al. , 2004), and the pattern of expression of the PDGF receptor in fetal and adult human testicular tissue is suggested to be comparable with that in rats (Basciani et al.…”
Section: Discussionmentioning
confidence: 99%
“…, 2006). As c‐kit is reported to be expressed in prepubertal human testis (Nicotina et al. , 2004), and the pattern of expression of the PDGF receptor in fetal and adult human testicular tissue is suggested to be comparable with that in rats (Basciani et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, clear signals of mRNA expression were detected in the human testis but neither the RNA nor the protein was detected in ejaculated spermatozoa. Expression of AQP1 in the normal human testis is restricted to the endothelial cells of blood vessels in normal tissue (Nicotina et al. , 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, clear signals of mRNA expression were detected in the human testis but neither the RNA nor the protein was detected in ejaculated spermatozoa. Expression of AQP1 in the normal human testis is restricted to the endothelial cells of blood vessels in normal tissue (Nicotina et al, 2004). Despite positive Western results in canine spermatozoa, where antibody specificity and protein localization still need to be demonstrated (Ito et al, 2008), the absence of AQP1 protein from murine (Lu et al, 2008) and ovine spermatozoa (Curry et al, 1995b) has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar observations were noticed in that study of Nurmio regarding the number of Sertoli cells as the number of Sertoli cells /cord cross section increased at PND70 as in our study as Sertoli cells do not show an expressing of c-kit or PDGFR receptors, so, Sertoli cells undergo proliferation as in normal states (35). Although the present study used the rat as an animal model, immature human testes is also susceptible to the impact of imatinib since c-kit is reported to show an expression in human testis at prepuberty (39) and the mode of expression of the PDGF receptor in human fetus and adult testicular section is similar to that in rats (31).…”
Section: Discussionmentioning
confidence: 99%